AGING: USE OF STRATEGIES, LEARNING AND RETENTION - Benedet, Mª Jesús; Martínez Arias, Rosario; Alejandre, Mª Angeles (Anales de Psicología / Annals of Psychology, 1998)
Using a semantically structured list of words, the usage of learning and recall strategies by a group of n=500 individuals 35 through 92-year-old, has been examined. The individuals were distributed into five age groups (35-44, 45-54, 55-64, 65-74, 75 and more). Regarding the learning essais, the three younger groups showed, on each of the variables considered, a quite similar curve, although values either decrease (on the positive variables) or increase (on the negative variable), respectively, as age increases. Regarding the recall tests (short and long delay, respectively), the 65-74 age group shows a diminished resistence to interference when compared with the two younger groups. On the other hand, the curves showed by the individuals aged 75 and more differe from the rest of the age group ones on every variable considered, both regarding the learning essais and the recall tests. Otherwise, the four groups benefit equally from the incitation to use a semantic strategy. The results are discussed from a neuropsychological approach, considering both, the available data about brain aging and a cognitive model of memory systems.